Empathy and social entrepreneurial intentions: Assessing the mediating and moderating roles of entrepreneurial behavior - Fulgencio, Nicole Isabel Verdeflor (Animo Repository, 2022)
It is evident that social entrepreneurship has been emerging in the Philippines, aiming to provide solutions to the different social issues present today. Several studies revealed that empathy is significant in predicting one’s social entrepreneurial intentions, however, the component of empathy was tackled as a whole, failing to take into account the specific factors that lead to one’s empathy. With this, the study utilized the Empathy Assessment Index composed of five variables to provide a better understanding and sufficient information about the component. The study examines the mediating and moderating roles of entrepreneurial behavior on the relationship between empathy and social entrepreneurial intentions. An online survey questionnaire was disseminated to 393 De La Salle University students via Google Forms, and the results were analyzed through statistical tools namely Jamovi and JASP. The findings revealed that entrepreneurial behavior fully mediated the relationship between empathy and social entrepreneurial intentions, implying that an increase in empathy will improve one’s personal attitude, subjective norms, and perceived behavioral control towards starting their own business, eventually leading to an increase in social entrepreneurial intention. Moreover, it was found that there was no moderating effect of entrepreneurial behavior on the relationship between empathy and social entrepreneurial intentions, hence no interaction among the variables.